Issues that mobilize Europe. The role of key policy issues for voter turnout in the 2019 European Parliament election. (March 2022) - Braun, Daniela; Schäfer, Constantin
In light of the unexpectedly high turnout in the 2019 European Parliament election, we explore how major transnational policy issues mobilize voters in European electoral contests. Based on the analysis of two data sets, the Eurobarometer post-election survey and the RECONNECT panel survey, we make three important observations. First, European citizens show a higher tendency to participate in European Parliament elections when they attribute greater importance to the issues 'climate change and environment', 'economy and growth', and 'immigration'. Second, having a more extreme opinion on the issue of 'European integration' increases people's likelihood to vote in European elections. Third, the mobilizing effect of personal issue importance is enhanced by the systemic salience that the respective policy issue has during the election campaign. These findings show the relevance of issue mobilization in European Parliament elections as well as its context-dependent nature.